The Uniqueness of Primogeniture in Traditional Inheritance Systems - Rozali, Ahmad; Marwin Marwin; Hidayat, Eko (Magister Hukum Universitas Semarang, 2025)
The uniqueness of primogeniture in traditional inheritance systems is urgent to examine, as it reflects enduring gendered power structures that persist amid legal modernization and evolving social norms. This research analyzes the uniqueness and resilience of the primogeniture inheritance system in traditional communities, particularly in Ratenggaro Traditional Village, Indonesia. It is situated within the legal pluralism context of Indonesia and the human rights-based critique of customary laws that prioritize male heirs. The study is urgent because modernization challenges traditional norms, demanding a reevaluation of gender equity in inheritance. Using a descriptive qualitative method with in-depth interviews and participant observation, this study finds that primogeniture governs not only material assets but also spiritual roles and kinship status. Despite modern pressure, elders uphold it as a symbol of identity and harmony. A unique finding is that although women do not inherit property, they are symbolically acknowledged through ritual practices involving gifts such as woven cloth and livestock. This study offers novelty by providing a legal-anthropological analysis of primogeniture in a remote indigenous context, contributing to discussions on legal pluralism, gender justice, and cultural sustainability. It suggests the need for dialogical reform that harmonizes adat law with constitutional equality.